A preparation method of double network hydrogel fracturing fluid based on click chemistry
The dual network hydrogel was generated through click chemical reactions, which solved the problem of difficult control of the polymer cross-linking speed and degree in oil field fracturing, and achieved a fracturing fluid with high viscoelasticity and excellent sand carrying capacity.
Patent Information
- Application Number
- CN202211290449.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-10-21
AI Technical Summary
The prior art is difficult to control the speed and degree of polymer cross-linking during the fracturing process of oil fields, resulting in insufficient viscoelasticity or poor fluidity, affecting the fracturing effect, and subsequently breaking of glue.
Using click chemical reaction, the polythio compound is crosslinked with polymers with unsaturated double bonds through thiol-ene Michael addition reaction to form a double network hydrogel.
The generated dual network hydrogel has good viscoelasticity and glue breaking ability, and is suitable as a fracturing fluid, showing excellent sand carrying ability and fracturing effect.
Smart Images

Figure BDA0003901140870000041 
Figure BDA0003901140870000051 
Figure BDA0003901140870000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oilfield oil production additives, and relates to a preparation method of a double network hydrogel fracturing fluid constructed based on click chemistry, and in particular to a preparation method of a double network hydrogel fracturing fluid obtained by click chemistry using N-allylmaleimide, N-vinylpyrrolidone, acrylamide, bisacrylamide polyethyleneimine, pentaerythritol tetrakis(3-mercaptopropionic acid), triethylamine and tris(hydroxymethylaminomethane) as main raw materials. Background Art
[0002] A certain viscoelasticity is one of the basic requirements of fracturing fluid. In order to increase the viscoelasticity of polymer solutions, various linear polymer molecules can be cross-linked in aqueous solution to form a three-dimensional network structure. The cross-linked polymer solution is a weak gel with a certain fluidity but no integrity and shape retention ability. When the concentration of polymer and cross-linker increases to a certain extent, a weak gel can be formed under certain conditions. Gel is a dispersed system with a network structure formed by the cross-linking reaction between the cross-linker and the functional groups on different polymer molecules. Its most significant feature is that the dispersed medium is completely contained in it. According to the goals and requirements of fracturing construction, polymers can be cross-linked into gels of different strengths and fluidities. The form formed by the cross-linking of polymer molecules depends on many factors such as solvent type, polymer properties, molecular weight and environmental conditions. Most current studies focus on evaluating the strength and stability of the cross-linked system by polymer type, polymer molecular weight, cross-linker, additives and their ratio under specific high temperature and high salt reservoir conditions. The optional cross-linking agents mainly include organic aluminum, organic chromium, polyhydroxy compounds, phenolic compounds and polyethylene imine. When cross-linking occurs between polyacrylamide molecules and cross-linking agents, the cross-linking speed and degree are difficult to control: if the cross-linking is too high, the fluidity of the cross-linked body will deteriorate, affecting the fracturing effect, and subsequent gel breaking will be difficult; if the cross-linking speed is too low, the viscoelasticity will be insufficient; and if the cross-linking speed is too fast or too slow, the fracturing construction will be affected. In addition, based on environmental protection and green chemistry requirements, oil fields are gradually abandoning cross-linked gels such as heavy metals, and new gels are one of the development directions of fracturing fluids. Summary of the invention
[0003] Click chemistry has many advantages such as simple reaction conditions, fast speed, high yield, environmental friendliness, and strong selectivity. The thiol-ene click chemistry reaction is a new type of click chemistry reaction developed in recent years, especially the thiol-ene can undergo a rapid Michael addition reaction under alkaline conditions. The inventors found that: using polythiol compounds through this click chemistry reaction, polymers with unsaturated double bonds can be rapidly cross-linked to generate hydrogels with good viscoelasticity; two linear polymer molecules containing unsaturated double bonds can be simultaneously cross-linked with polythiol compounds through Michael addition click chemistry in aqueous solution, thereby generating a double network gel system; the double network hydrogel generated by the click chemistry reaction has good viscoelasticity, and can also be quickly broken under acidic conditions, and as a fracturing fluid, it exhibits ideal fracturing and sand carrying performance. The purpose of the present invention is to provide a preparation method for a double network hydrogel fracturing fluid constructed based on click chemistry, and the specific technical scheme is as follows.
[0004] A method for preparing a double network hydrogel fracturing fluid based on click chemistry comprises the following steps:
[0005] Step (1): preparing a ternary linear copolymer containing maleimide side groups by free radical initiation using N-allylmaleimide, N-vinylpyrrolidone and acrylamide in a certain ratio;
[0006] Step (2): adding a certain proportion of bisacrylamide polyethyleneimine, triethylamine and tris(hydroxymethyl)aminomethane to the terpolymer containing maleimide side groups obtained in step (1), respectively, and mixing to obtain a solution;
[0007] Step (3): dispersing a certain amount of pentaerythritol tetrakis(3-mercaptopropionic acid) ester in the solution obtained in step (2) and mixing them thoroughly; pentaerythritol tetrakis(3-mercaptopropionic acid) ester is respectively covalently cross-linked with a ternary linear copolymer molecule containing maleimide and a bisacrylamide polyethyleneimine molecule containing an unsaturated double bond through a mercapto-ene Michael addition click chemistry reaction, thereby finally generating a double-network hydrogel fracturing fluid.
[0008] Furthermore, in step (1), the molar ratio of N-allylmaleimide, N-vinylpyrrolidone and acrylamide is (4-6):(8-10):(60-80).
[0009] Furthermore, the specific conditions for free radical initiation in step (1) are: dissolving N-allylmaleimide, N-vinylpyrrolidone and acrylamide in distilled water, adding an initiator, cooling to 2-6°C, introducing an inert gas for protection, heating to 30-40°C for reaction for 7-9h, and cooling to room temperature. Preferably, the inert gas is nitrogen or argon. Preferably, the initiator is potassium persulfate and disodium ethylenediaminetetraacetate.
[0010] Furthermore, in step (2), the average degree of polymerization of the bisacrylamide polyethylene imine is 90-110, and the molar ratio of the bisacrylamide polyethylene imine, triethylamine and tris(hydroxymethyl)aminomethane is (1.5-2.5):(12-18):(3-5). Furthermore, the molar ratio of the bisacrylamide polyethylene imine added in step (2) to the acrylamide added in step (1) is 1:(450-550).
[0011] Furthermore, the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester added in step (3) to acrylamide added in step (1) is 1:(200-220).
[0012] Furthermore, the click chemistry reaction conditions in step (3) are: reaction temperature 40-50° C., reaction time 10-20 min.
[0013] The preparation method provided by the present invention has mild conditions, and the obtained double-network-containing hydrogel has good rheological characteristics as a fracturing fluid, exhibits high viscoelasticity, excellent sand-carrying capacity and gel-breaking ability, and has broad application prospects in the field of fracturing construction. DETAILED DESCRIPTION
[0014] The technical solution of the present invention is described clearly and completely below. Obviously, the described implementation is only a part of the implementation of the present invention, not all of the implementation. Based on the implementation of the present invention, all other implementations obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0015] Example 1
[0016] A method for preparing a double network hydrogel fracturing fluid based on click chemistry comprises the following steps:
[0017] Step (1): add 15.0 g acrylamide, 3.0 g N-vinyl pyrrolidone and 2.0 g N-allyl maleimide into 100 mL distilled water, and stir to dissolve; then add 0.005 g potassium persulfate and 0.005 g disodium ethylenediaminetetraacetate, and stir to dissolve; pour the above solution into a glass reaction bottle, cool to 4° C., introduce nitrogen for 15 minutes, seal the reaction bottle, and then heat to 35° C. to initiate polymerization, react for 8 hours, and cool to room temperature to generate a light yellow transparent rubber block; weigh 10.0 g of the above rubber block, cut it into small particles, place it in 500 ml of clean water, and stir for 24 hours to obtain a colorless, transparent, viscous solution for standby use;
[0018] Step (2): add 0.2 g of bisacrylamide polyethyleneimine with an average polymer of 100, 0.03 g of triethylamine and 0.01 g of tris(hydroxymethyl)aminomethane to 20 ml of clean water, stir and dissolve to obtain a light yellow uniform liquid for standby use;
[0019] Step (3): the colorless, transparent, viscous solution obtained in step (1) and the light yellow uniform liquid obtained in step (2) are fully mixed, and then 0.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester is added. After fully mixing, the temperature is raised to 45° C. and reacted for 15 minutes to generate a light yellow colloid, which is a double network hydrogel.
[0020] Example 2
[0021] A method for preparing a double network hydrogel fracturing fluid based on click chemistry comprises the following steps:
[0022] Step (1): add 14.2 g acrylamide, 2.6 g N-vinyl pyrrolidone and 1.5 g N-allyl maleimide into 100 mL distilled water and stir to dissolve; then add 0.005 g potassium persulfate and 0.005 g disodium ethylenediaminetetraacetate and stir to dissolve; pour the above solution into a glass reaction bottle, cool to 2° C., introduce argon for 15 minutes, seal the reaction bottle, and then heat to 30° C. to initiate polymerization, react for 9 hours, cool to room temperature, and generate a light yellow transparent rubber block; weigh 10.0 g of the above rubber block, cut it into small particles, place it in 500 ml of clean water, stir for 24 hours, and obtain a colorless, transparent, viscous solution for standby use;
[0023] Step (2): add 0.2 g of bisacrylamide polyethyleneimine with an average polymer of 90, 0.02 g of triethylamine and 0.01 g of tris(hydroxymethyl)aminomethane to 20 ml of clean water, stir and dissolve to obtain a light yellow uniform liquid for standby use;
[0024] Step (3): the colorless, transparent, viscous solution obtained in step (1) and the light yellow uniform liquid obtained in step (2) are fully mixed, and then 0.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester is added. After fully mixing, the mixture is heated to 40° C. and reacted for 20 minutes to generate a light yellow colloid, which is a double network hydrogel.
[0025] Example 3
[0026] A method for preparing a double network hydrogel fracturing fluid based on click chemistry comprises the following steps:
[0027] Step (1): add 15.6 g acrylamide, 3.4 g N-vinyl pyrrolidone and 2.6 g N-allyl maleimide into 100 mL distilled water, and stir to dissolve; then add 0.005 g potassium persulfate and 0.005 g disodium ethylenediaminetetraacetate, and stir to dissolve; pour the above solution into a glass reaction bottle, cool to 6° C., introduce nitrogen for 15 minutes, seal the reaction bottle, and then heat to 40° C. to initiate polymerization, react for 7 hours, and cool to room temperature to generate a light yellow transparent rubber block; weigh 10.0 g of the above rubber block, cut it into small particles, place it in 500 ml of clean water, and stir for 24 hours to obtain a colorless, transparent, viscous solution for standby use;
[0028] Step (2): add 0.2 g of bisacrylamide polyethyleneimine with an average polymer of 110, 0.04 g of triethylamine and 0.01 g of tris(hydroxymethyl)aminomethane to 20 ml of clean water, stir and dissolve to obtain a light yellow uniform liquid for standby use;
[0029] Step (3): the colorless, transparent, viscous solution obtained in step (1) and the light yellow uniform liquid obtained in step (2) are fully mixed, and then 0.5 g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester is added. After fully mixing, the temperature is raised to 50° C. and reacted for 10 minutes to generate a light yellow colloid, which is a double network hydrogel.
[0030] Example 4
[0031] The viscosity of the light yellow colloid obtained in Example 1 at five temperatures of 30°C, 60°C, 90°C, 120°C and 150°C was measured using a BROOKFILD DV-III+ rheometer; the results are shown in Table 1.
[0032] Table 1 Viscosity of the light yellow colloid obtained in Example 1 (mPa·s)
[0033] Temperature, °C 30 60 90 120 150 Viscosity, mPa·s 1225 1184 1029 886 810
[0034] The light yellow colloid obtained in Example 1 has relatively high viscosity at three temperatures of 90° C., 120° C. and 150° C., indicating that the light yellow colloid obtained in Example 1 has good temperature resistance.
[0035] Example 5
[0036] When the formation pressure is constant, the greater the friction of the fracturing fluid in the pipeline, the greater the pressure required by the pump. When the resistance is too large and the gel stability is insufficient, the elasticity of the gel decreases, and the gel may even be destroyed, resulting in ineffective fracturing. Therefore, the elasticity and stability of the gel are the basis for ensuring effective fracturing.
[0037] At a shear rate of 170 s -1At a temperature of 150° C., the storage modulus and loss modulus of the light yellow colloid obtained in Example 1 were measured as the shear time increased. The results are shown in Table 2.
[0038] Table 2 Storage modulus and loss modulus at 150℃ with shear time (shear rate 170s -1 )
[0039]
[0040]
[0041] At a fixed temperature of 150 °C and a shear rate of 170 s -1 Under the conditions, as the shear time increases, the storage modulus and loss modulus of the light yellow colloid obtained in Example 1 decrease, but the decrease is not large, and the storage modulus is still much larger than the loss modulus, indicating that the solution has good stability and good viscoelasticity.
[0042] Example 6
[0043] In order to prevent sand jam or sand plugging during construction, the fracturing fluid system should have good sand carrying capacity. Under the same construction displacement and process, the higher the viscoelasticity of the fracturing fluid, the better the sand carrying capacity. The sand carrying capacity is the result of the combined effect of viscous suspended sand and elastic suspended sand.
[0044] Take a stoppered measuring cylinder with a length of 100 cm and an inner diameter of 4.5 cm, a stopwatch and ceramsite with a particle size of 0.425-0.850 mm for use. Add ceramsite to the light yellow colloid obtained in Example 1 at a volume ratio of 70 / 30, stir and mix thoroughly, pour the mixed solution into the measuring cylinder, and place the measuring cylinder in a 30°C glass water bath to measure the sedimentation rate of ceramsite sand particles, repeat three times and take the average value. The sedimentation rate of ceramsite sand particles at 60°C and 90°C was measured respectively by the same method as above, and the results are shown in Table 3.
[0045] Table 3 Sedimentation rate of ceramsite with a particle size of 0.425-0.850 mm in the light yellow colloid obtained in Example 1 at different temperatures
[0046] Temperature, °C 30 60 90 Sedimentation velocity, cm / min 0.071 0.088 0.10
[0047] The results show that the lower the temperature, the smaller the sedimentation rate of ceramsite in the light yellow colloid obtained in Example 1, and vice versa. For example, at a temperature of 60°C and a sand ratio of 70 / 30, the sedimentation rate of ceramsite in the light yellow colloid obtained in Example 1 is 0.088 cm / min, indicating that the light yellow colloid obtained in Example 1 has a good sand carrying capacity.
[0048] Example 7
[0049] Take 100g of the light yellow colloid obtained in Example 1, add 0.1g, 0.15g and 0.2g of ammonium persulfate respectively, mix well, pour into a wide-mouth bottle, and measure the viscosity of the degelling liquid after standing at 60°C for different time. Repeat the above experiment in the same way, measure the viscosity of the degelling liquid after standing at 90°C for different time, and the results are shown in Tables 4 and 5.
[0050] Table 4 Viscosity of the light yellow colloid solution obtained in Example 1 after different degelling times at 60°C
[0051]
[0052]
[0053] Table 5 Viscosity of the light yellow colloid solution obtained in Example 1 after degelling for different times at 90°C
[0054]
[0055] It can be seen from Tables 4 and 5 that ammonium persulfate has a good gel breaking ability for the light yellow colloid obtained in Example 1.
[0056] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention. The protection scope of the present invention is defined by the claims and their equivalent technical solutions.
Claims
1. A method for preparing a double network hydrogel fracturing fluid based on click chemistry, characterized in that: The following steps are involved: Step (1): preparing a ternary linear copolymer containing maleimide side groups by free radical initiation using N-allylmaleimide, N-vinylpyrrolidone and acrylamide in a certain ratio, wherein the molar ratio of N-allylmaleimide, N-vinylpyrrolidone and acrylamide is (4-6): (8-10): (60-80); Step (2): adding a certain proportion of bisacrylamide polyethylene imine, triethylamine and trimethylolaminomethane to the terpolymer containing maleimide side groups obtained in step (1), and mixing to obtain a solution; the average polymerization degree of bisacrylamide polyethylene imine is 90-110, the molar ratio of bisacrylamide polyethylene imine, triethylamine and trimethylolaminomethane is (1.5-2.5): (12-18): (3-5); the molar ratio of bisacrylamide polyethylene imine to acrylamide added in step (1) is 1: (450-550); Step (3): dispersing a certain amount of pentaerythritol tetrakis(3-mercaptopropionic acid) ester in the solution obtained in step (2) and mixing them thoroughly, wherein the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester to acrylamide added in step (1) is 1:(200-220); pentaerythritol tetrakis(3-mercaptopropionic acid) ester is covalently cross-linked with a ternary linear copolymer molecule containing maleimide and a bisacrylamide-based polyethyleneimine molecule containing an unsaturated double bond through a mercapto-ene Michael addition click chemistry reaction, thereby finally generating a double network hydrogel fracturing fluid.
2. The preparation method according to claim 1, characterized in that: The specific conditions for free radical initiation in step (1) are as follows: dissolve N-allylmaleimide, N-vinylpyrrolidone and acrylamide in distilled water, add initiator, cool to 2-6°C, introduce inert gas protection, heat to 30-40°C, react for 7-9h, and cool to room temperature.
3. The preparation method according to claim 2, characterized in that: The inert gas is nitrogen or argon.
4. The preparation method according to claim 2, characterized in that: The initiators are potassium persulfate and disodium ethylenediaminetetraacetate.
5. The preparation method according to claim 1, characterized in that: The click chemistry reaction conditions in step (3) are: reaction temperature 40-50°C, reaction time 10-20 min.
Citation Information
Patent Citations
Humidity-resistant self-suspending proppants
CN106103891A
Seawater-based thickening agent for fracturing as well as preparation method and application thereof
CN106433600A